The impending educational transformation in the face of Artificial Intelligence - Cuevas Gómez, Martha Elena (Emerging Trends in Education, 2024)
The digital culture implies the development of digital knowledge that requires a permanent updating for technological appropriation from universities, said Dr. Alberto Ramirez Martinell, Researcher at the Center for Research and Innovation in Higher Education of the Universidad Veracruzana. Interviewed in the framework of the National Congress of Educational Research, the General Coordinator of the States of Knowledge of the Mexican Council of Educational Research, said that the challenges of education have displaced some priorities for others, according to the social reality in technological advances.